A retrospective study of variations in the kinds of diseases discharged from the Department of Infectious Diseases of a large general hospital in Central China during 2013–2019 - Ye, Pian; Zhao, Lei; Pang, Ran; Zheng, Xin (Frontiers in Public Health, 2024)
Objective: To analyze the changing trend of the absolute number and constituent ratio of various in-patient diseases in the Department of Infectious Diseases of a large general hospital in Central China during 2013-2019. Methods: A retrospective study was conducted to analyze the diagnostic data of discharged patients for seven consecutive years, from 2013 to 2019. The first discharge diagnosis is used as the basis for the disease classification. The absolute number, constituent ratio, and changing trend of major diseases in hepatobiliary diseases and infectious diseases were analyzed. Results: The changing trend of the diseases during 2013-2019 showed that the absolute number of cases of hepatobiliary disease did not change significantly (p = 0.615), while the constituent ratio decreased significantly, from 68.01% in 2013 to 55.29% in 2019 (P＜0.001). The absolute number (constituent ratio) of cases of infectious diseases increased significantly from 585(21.91%) in 2013 to 1244(36.86%) in 2019 (p = 0.015, P＜0.001). The major part of the increase was non-communicable infectious diseases (NCIDs). Conclusion: During 2013-2019, the proportion of cases of hepatobiliary disease gradually decreased. The absolute number and proportion of cases of infectious diseases, especially NCIDs, have increased rapidly.